Euro-Par 2009 Parallel Processing 15th International Euro-Par Conference, Delft, The Netherlands, August 25-28, 2009. Proceedings - Sips, Henk.; Epema, Dick.; Lin, Hai-Xiang.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
This book constitutes the refereed proceedings of the 15th International Conference on Parallel Computing, Euro-Par 2009, held in Delft, The Netherlands, in August 2009. The 85 revised papers presented were carefully reviewed and selected from 256 submissions. The papers are organized in topical sections on support tools and environments; performance prediction and evaluation; scheduling and load balancing; high performance architectures and compilers; parallel and distributed databases; grid, cluster, and cloud computing; peer-to-peer computing; distributed systems and algorithms; parallel and distributed programming; parallel numerical algorithms; multicore and manycore programming; theory and algorithms for parallel computation; high performance networks; and mobile and ubiquitous computing.
Abstracts Invited Talks -- Topic 1: Support Tools and Environments -- Topic 2: Performance Prediction and Evaluation -- Topic 3: Scheduling and Load Balancing -- Topic 4: High Performance Architectures and Compilers -- Topic 5: Parallel and Distributed Databases -- Topic 6: Grid, Cluster, and Cloud Computing -- Topic 7: Peer-to-Peer Computing -- Topic 8: Distributed Systems and Algorithms -- Topic 9: Parallel and Distributed Programming -- Topic 10: Parallel Numerical Algorithms -- Topic 11: Multicore and Manycore Programming -- Topic 12: Theory and Algorithms for Parallel Computation -- Topic 13: High-Performance Networks -- Topic 14: Mobile and Ubiquitous Computing.
Keywords: Computer science; Computer organization; Microprocessors; Computer communication systems; Computer system failures; Architecture, Computer; Operating systems (Computers).; Computer Science; Computer System Implementation; Computer Systems Organization and Communication Networks; System Performance and Evaluation; Processor Architectures; Computer Communication Networks; Operating Systems; Electronic books